Outcomes of anticoagulated patients with atrial fibrillation treated with or without antiplatelet therapy - A pooled analysis from the PREFER in AF and PREFER in AF PROLONGATON registries. (1st November 2018) - Patti, Giuseppe; Pecen, Ladislav; Lucerna, Markus; Huber, Kurt; Rohla, Miklos; Renda, Giulia; Siller-Matula, Jolanta; Schnabel, Renate B.; Cemin, Roberto; Kirchhof, Paulus; De Caterina, Raffaele
Abstract: Background: Evidence on whether antiPLT added to OACs is of advantage in atrial fibrillation (AF) patients with concomitant stable coronary artery disease (CAD) is limited. We evaluated clinical outcomes with oral anticoagulant (OAC) monotherapy vs antiplatelet therapy (antiPLT) plus OAC in patients with AF and stable CAD. Methods: Data on 1058 AF patients on OACs and history (>1 year) of myocardial infarction or coronary stenting were pooled from the PREFER-in-AF and PREFER-in-AF PROLONGATION registries. We primarily compared the 1-year incidence of a net composite endpoint (primary endpoint), including acute coronary syndrome and major bleeding, with or without antiPLT. Results: The incidence of the primary net composite endpoint was significantly higher in patients receiving OACs + antiPLT ( N = 348) vs OACs alone ( N = 710): 7.9 vs 4.2 per 100 patients/year; adjusted OR [95% CI] 1.84 [1.01–3.37]; p = 0.048. Among the components of the primary endpoint, the greatest relative difference was found for major bleeding (OR [95% CI] 2.28 [95% CI 1.00–5.19]), and especially life-threatening or non-gastrointestinal bleeding. The net clinical outcome with OACs + antiPLT was poorer irrespective of the type of CAD (previous infarction or coronary stenting), the type of stent (bare metal or drug-eluting) or the type of OAC (vitamin K antagonist or non-vitamin K antagonist OAC). Conclusions: Among patients with AF and stable CAD >1-year after the index event, the addition of antiPLT to OAC does not apparently provide added protection against coronary events, but increases major bleeding. OAC monotherapy should thus be considered the antithrombotic therapy of choice for such patients. Highlights: Evidence on optimal antithrombotic therapy in AF patients with CAD (MI or coronary stenting >1 year) is limited. We found that antiPLT added to OAC did not provide protection against coronary events, but increased major bleeding. These results were consistent regardless of the type of OAC (VKAs vs NOACs). OAC monotherapy should be the antithrombotic therapy of choice for such patients.